How to Effect Social Media Marketing Mediated by Brand Trust on Donation Decision - Adelia Dwi Putri; Ari Anggarani Winadi Prasetyoning Tyas (Formosa Journal of Sustainable Research, 2023)
This research intends to examine how Social Media Marketing impacts Donation Decision Mediated by Brand Trust at Kitabisa.com. Social Media Marketing as exogenous variable, Brand Trust as mediating variable and Donation Decision as endogenous variable. This research was conducted on social media users who have donated to Kitabisa.com who were found in the West Jakarta area. The background of this research is the changes in people's behavior who have started to do various things, including donating activities using technology and the internet because they are able to provide convenience in doing these things, which has resulted in various new innovations to channel donations online emerging from those who see this as an opportunity. This research about utilized tests taken by purposive sampling technique utilizing Hair computation strategy as numerous as 145 respondents. The analytical technique utilized is the Structural Equation Model (SEM) and uses Partial Least Square (PLS) to test the quality of direct and indirect connections among various variables. The comes of this exploration demonstrate that Social Media Marketing has an impact on Donation Decision, Brand Trust influences Donation Decision, Social Media Marketing has an effect on Brand Trust, and Social Media Marketing affects Donation Decision through Brand Trust